2012
DOI: 10.1007/s00038-012-0433-2
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Global Youth Tobacco Survey and implementation of WHO Framework Convention on Tobacco Control in former Soviet Union countries

Abstract: Overall, our study shows that FSU countries had positive changes in tobacco-use prevalence and perception among youth over time. Our findings should be used as baseline measures for future tobacco-control interventions aimed at reducing tobacco use among youth. Moreover, our results call for the enforcement of restricting advertising for tobacco products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The Global Tobacco Surveillance System launched during 1999-2006 in 132 countries shows that 44% of children up to 15 years and 42% of young people aged 16-19 years are exposed to the harmful effects of tobacco smoke in their home [22]. The Global Youth Tobacco Survey studies have shown that exposure to environmental tobacco smoke can be up to 90% [17,23]. Our study showed decrease in the prevalence of smoking by parents.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The Global Tobacco Surveillance System launched during 1999-2006 in 132 countries shows that 44% of children up to 15 years and 42% of young people aged 16-19 years are exposed to the harmful effects of tobacco smoke in their home [22]. The Global Youth Tobacco Survey studies have shown that exposure to environmental tobacco smoke can be up to 90% [17,23]. Our study showed decrease in the prevalence of smoking by parents.…”
Section: Discussionmentioning
confidence: 53%
“…According to the adolescent subjects, their parents frequently smoked in the presence of household members: 24% of secondary school students' parents and 36% of high school students' parents did so. group, the average number of cigarettes smoked per day was 14 [17]. In our 2009 study, 22% of secondary school students and 28% of high school students smoked > 10 cigarettes daily.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Previously, a paper was presented regarding implementation of the WHO FCTC in the former Soviet Union [24]. The purpose of this paper is to use the data that has been collected in the GYTS conducted in EMR countries to set the baseline and monitor changes in tobacco use among youth and monitor the WHO FCTC articles.…”
Section: Introductionmentioning
confidence: 99%
“…More surprising, however, is the large number of low-and middle-income countries which have introduced such bans (Christopoulou et al 2013;Feldman and Bayer 2011;Usmanova and Mokdad 2013). In fact, in the only other previous study to use a globally representative sample (N = 100-117) to investigate the determinants of smoke-free laws, it was found that less wealthy countries actually were more likely to have bans in place prior to the FCTC in the early 2000s (Gallet 2009).…”
Section: Introductionmentioning
confidence: 99%